KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN PADA HOTEL SWISSBELL AMBON - Victry Erlitha Picauly; Stevie Sahusilawane; Geradin Rehatta; Yuliati Anmama (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2020)
This study aims to determine the effect of physical evidence, reliability, responsiveness, assurance, and attention to tourist satisfaction partially and simultaneously. The research method used in this research is explanatory research. Analysis of the data used is multiple regression processed using SPSS. The study population was all visitors who stayed at Swissbell Hotel in July 2017. The sample of this study was taken using a purposive sampling method to obtain a sample of 50 tourists. The results showed that in partial testing physical evidence, reliability, responsiveness, assurance, and attention had a positive effect on tourist satisfaction. Simultaneously physical evidence, reliability, responsiveness, assurance, and attention affect tourist satisfaction.